2015
DOI: 10.4067/s0718-16202015000100001
|View full text |Cite
|
Sign up to set email alerts
|

Finishing strategies for steers based on pasture or silage plus grain and time on feed and their effects on beef quality

Abstract: The physicochemical and sensory attributes and the fatty acid composition of the longissimus lumborum muscle were determined. The beef from pasture-fed animals tended to be tenderer, darker, less red, and with yellower fat than the beef from grain-fed steers. The beef from steers fed wheat plus silage for 75 d had lower tenderness scores than beef from steers fed for 35 d on grain plus silage. The beef from pasture-fed steers had higher levels of conjugated linoleic acid c-9 t-11 and n-3 fatty acids and a lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
1
4
1
1
Order By: Relevance
“… Demirel et al (2006) indicated that it is difficult to increase the P/S ratio when ruminants are fed either grass hay or concentrate, whereas the n-6/n-3 ratio in meat is more influenced by the diet. Similar n-6/n-3 ratios have been reported by other authors in grass-fed beef ( Schor et al, 2008 ; De la Fuente et al, 2009 ; Aldai et al, 2011 ; Morales et al, 2012 , 2015 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… Demirel et al (2006) indicated that it is difficult to increase the P/S ratio when ruminants are fed either grass hay or concentrate, whereas the n-6/n-3 ratio in meat is more influenced by the diet. Similar n-6/n-3 ratios have been reported by other authors in grass-fed beef ( Schor et al, 2008 ; De la Fuente et al, 2009 ; Aldai et al, 2011 ; Morales et al, 2012 , 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study meat from steers showed higher content of intramuscular fat compared to meat from calves. However, meat from both, steers and calves, was leaner in comparison with intramuscular fat content previously reported from steers finished on temperate pastures (2.21% to 2.42%; Morales et al, 2012 , 2015 ), and from dairy bulls finished on concentrates (1.94%, Catrileo et al, 2014 ) in the South of Chile. The intramuscular fat content has been shown to be directly related to the extent of concentrate-finishing period ( Wood et al, 2008 ).…”
Section: Discussioncontrasting
confidence: 51%
“…En cuanto a la calidad, posee características propias de una carne producida a pastoreo como un bajo contenido de grasa intramuscular (2%-3%), una relación entre los ácidos grasos omega-3 y omega-6 inferior a 4, y un contenido de ácido linoleico mayor que la carne obtenida a partir de otros sistemas de alimentación (Morales et al, 2012;Morales et al, 2015), siendo estos parámetros de calidad una ventaja comparado a otros modos de producción de carne bovina.…”
Section: Modo De Producciónunclassified
“…Some studies report that, as a result of drastic climate change, the animals in the northern region of Mexico have periods of 90 to 100 days of favorable grazing conditions, and if the number of days is reduced, the survival of these animals may be in danger (Navarro et al, 2002). In general terms, the nutritional value of forage is the result of intrinsic plant factors such as the chemical composition, digestibility, and environmental factors, as well as the inherent factors of the animal and the interaction between the forages, the animals and the environment (Balseca et al, 2015;Morales et al, 2015). Under long-term drought conditions, the evaluation of the chemical composition of the diet of grazing cattle acquires relevance due to the seasonal variations in the nutrient content of the diet selected by the animals.…”
Section: Introductionmentioning
confidence: 99%